A finite element-based subspace fitting approach for structure identification and damage localization. (June 2015) - Gautier, G.; Mencik, J.-M.; Serra, R.
Abstract: A finite element-based subspace fitting approach is proposed for the identification of vibrating structures. The approach makes use of the subspace-based state space system identification (4SID) methods which aim at assessing a so-called extended observability matrix from the knowledge of experimental measurement data. The feature of the present work concerns the use of a finite element model updating procedure to identify the structure parameters accurately when the number of output sensors is small. Besides, an algorithm procedure is proposed which, once combined with the finite element-based subspace fitting approach, provides an accurate and fast way to localize damages in structures. This involves an iterative domain partitioning scheme of a coarse finite element mesh, as well as a subdomain updating technique. The relevance of the proposed approaches is highlighted through the following test cases: (i) a numerical beam, based on a 3D finite element mesh, containing single or double notches; (ii) an experimental beam containing a single notch. Abstract : Highlights: A subspace fitting approach is proposed for structure identification and damage localization. The 4SID technique combined with a FE model updating procedure is used. An iterative domain partitioning procedure is carried out to localize damages. Numerical and experimental beams that contain single or multiple notches are analyzed. The relevance of the approach, in terms of accuracy and computational savings, is highlighted.